ANALISIS PENERAPAN GREEN COMPUTING PADA PERGURUAN TINGGI BERBASIS TEKNOLOGI INFORMASI - Klaudius Jevanda BS; Marcelius Michael Livinus (Jurnal Ilmiah Matrik, 2019)
Abstract : This study aims to determine the level of application of green computing at the Universitas Katolik Musi Charitas Palembang and recommend strategies in implementing green computing. Where green computing itself is the study and realization of the use of computing resources efficiently and environmentally friendly. The purpose of green computing is to increase the efficiency of use and reduce energy consumption and carbon footprint. Universitas Katolik Musi Charitas Palembang has long been using Information Technology (IT), one of which is a computer to support the ongoing process of the academic community. But the use of computers unwittingly provides a big role in environmental pollution and CO2 emissions. Based on the results of research that still needs to be socialized about understanding the importance of management and utilization in the use of IT equipment and policies to support the reduction of energy consumption and environmental pollution.